THE OUTSTANDING OPERA SINGERS SOLOMIYA KRUSHELNYTSKA AND MYKHAILO GOLYNSKY IN THE VASYL STEFANYK`S LIFE - Karas, Hanna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
One of the peculiarities in the studying of the Vasyl Stefanik’s creative life is his relationships with the prominent Ukrainian singers Solomiya Krushelnytska (1872–1952) and Mykhailo Golynsky (1890–1973). Having strong national and cultural identity and talent they filled the artist’s spiritual life with new colors, impressions, and feelings. Being all-arounder personalities the singers paid tribute to the writer’s talent, supported him in his difficult period of life. One of Solomiya Krushelnytska, as one of the most famous women of ancient and modern Ukraine, made a strong impression on the young Vasyl Stefanyk. He was fascinated by her talent, beauty, temperament, and praised Solomiya' s voice and intellect. The writer carried this reverence for the singer throughout his life. Vasyl Stefanyk’s relationship with Mykhailo Golynsky was of a different nature. A native of Horodenka region, which borders the Sniatyn region, the peasant’s son Mykhailo, like Vasyl Stefanyk, was a great patriot of Ukraine, a romantic who dreamed of singing for his people. He was applauded by Lviv and Warsaw, Torun and Berlin, Kharkiv and Kyiv, New York, Ottawa and Winnipeg. He was compared to the great Caruso. As a relative of Marko Cheremshyna (Ivan Semanyuk), Mykhailo often visited him in Sniatyn. Vasyl Stefanyk also came here from Rusov. While in Soviet Ukraine in 1926–1930 (Odesa, Kyiv, Kharkiv), the singer became a link between Ukrainian writers and V. Stefanyk, who conveyed greetings to the Galician novelist and wished to meet him. Gaining prestige after his triumphant speeches in Kharkiv (then the capital of Ukraine), M. Golynsky, fulfilling the request of Professor Kyrylo Studynsky, appealed to the Minister of Education M. Skrypnyk with a request for financial assistance for Vasyl Stefanyk. In 1928, the Soviet government granted him a personal pensionfor propaganda purposes, and in 1931 he celebrated his 60th birthday in Kharkiv. M. Golynsky took part in the writer' s jubilee on June 17, 1927 in the People' s House in Lviv. The article’s key sources are the epistolary and memoir heritage of these extraordinary individuals.